Biocatalysis as Key to Sustainable Industrial Chemistry. Issue 9 (21st April 2022) - Alcántara, Andrés R.; Domínguez de María, Pablo; Littlechild, Jennifer A.; Schürmann, Martin; Sheldon, Roger A.; Wohlgemuth, Roland
Abstract: Invited for this month′s cover is the Working Group Sustainable Chemistry of the European Society of Applied Biocatalysis (ESAB). The image shows the significant contributions of Biocatalysis to science, industry, society, and environment as a technology of first choice for Sustainable Chemistry in the 21st century. The Perspective itself is available at 10.1002/cssc.202102709 . Abstract : "A "Golden Age" of biocatalysis is on the horizon…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202102709 . View the Front Cover here: 10.1002/cssc.202200707 .